The Influence of Thrombin on the Platelet-Aggregating Activity of Human Factor VIII. A Study with Insolubilized Thrombin - Vukovich, Th; Koller, E; Doleschel, W (Thrombosis and Haemostasis, 1979)
A study was made of the influence of thrombin on the platelet-aggregating activity of human factor VIII with Ristocetin as cofactor. Purified factor VIII and different amounts of a thrombin-Sepharose 2B complex were mixed and incubated for various periods of time. The factor VIII-related platelet-aggregating activities of the filtrates of the incubation mixtures were determined in a test system using formalin-fixed platelets and Ristocetin as cofactor. The results so obtained indicate that thrombin inactivates the platelet-aggregating activity of factor VIII. The filtrates of the incubation mixtures were also tested by a two- stage test system for their clotting activities. Comparison of the influence of thrombin on the clotting- and the platelet-aggregating activities of factor VIII is presented and discussed.